Ratiometric Upconversion Temperature Sensor Based on Cellulose Fibers Modified with Yttrium Fluoride Nanoparticles - Małgorzata Skwierczyńska; Natalia Stopikowska; Piotr Kulpiński; Magdalena Kłonowska; Stefan Lis; Marcin Runowski (Nanomaterials, 2022)
In this study, an optical thermometer based on regenerated cellulose fibers modified with YF3: 20% Yb3+, 2% Er3+ nanoparticles was developed. The presented sensor was fabricated by introducing YF3 nanoparticles into cellulose fibers during their formation by the so-called Lyocell process using N-methylmorpholine N-oxide as a direct solvent of cellulose. Under near-infrared excitation, the applied nanoparticles exhibited thermosensitive upconversion emission, which originated from the thermally coupled levels of Er3+ ions. The combination of cellulose fibers with upconversion nanoparticles resulted in a flexible thermometer that is resistant to environmental and electromagnetic interferences and allows precise and repeatable temperature measurements in the range of 298–362 K. The obtained fibers were used to produce a fabric that was successfully applied to determine human skin temperature, demonstrating its application potential in the field of wearable health monitoring devices and providing a promising alternative to thermometers based on conductive materials that are sensitive to electromagnetic fields.